2005
DOI: 10.1073/pnas.0500749102
|View full text |Cite
|
Sign up to set email alerts
|

JNK regulates lifespan in Caenorhabditis elegans by modulating nuclear translocation of forkhead transcription factor/DAF-16

Abstract: DAF-16͞forkhead transcription factor, the downstream target of the insulin-like signaling in Caenorhabditis elegans, is indispensable for both lifespan regulation and stress resistance. Here, we demonstrate that c-Jun N-terminal kinase (JNK) is a positive regulator of DAF-16 in both processes. Our genetic analysis suggests that the JNK pathway acts in parallel with the insulin-like signaling pathway to regulate lifespan and both pathways converge onto DAF-16. We also show that JNK-1 directly interacts with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
406
2
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(431 citation statements)
references
References 31 publications
20
406
2
3
Order By: Relevance
“…On the other hand, in response to stress, MST1 (Lehtinen et al, 2006) and JNK1 (Essers et al, 2004) phosphorylate FOXO factors at different sites, resulting in nuclear translocation and transactivation. Similar results were also observed in C. elegans, in that DAF-16 is phosphorylated by JNK in response to heat shock, and promotes the translocation of DAF-16 into the nucleus (Oh et al, 2005). Acetylation on the lysine residue neutralizes the positive charge and reduces FOXO DNA-binding affinity (Matsuzaki et al, 2005).…”
Section: Introductionsupporting
confidence: 74%
“…On the other hand, in response to stress, MST1 (Lehtinen et al, 2006) and JNK1 (Essers et al, 2004) phosphorylate FOXO factors at different sites, resulting in nuclear translocation and transactivation. Similar results were also observed in C. elegans, in that DAF-16 is phosphorylated by JNK in response to heat shock, and promotes the translocation of DAF-16 into the nucleus (Oh et al, 2005). Acetylation on the lysine residue neutralizes the positive charge and reduces FOXO DNA-binding affinity (Matsuzaki et al, 2005).…”
Section: Introductionsupporting
confidence: 74%
“…jnk-1 overexpression enhances the lifeextending effect of a daf-2 hypomorphic mutation, suggesting that JNK-1 regulates lifespan in parallel to the insulin-/IGF-1 pathway, with both pathways converging on DAF-16. JNK-1 regulates lifespan by directly interacting with DAF-16 and modulating its nuclear translocation (Oh et al, 2005). In Drosophila, JNK activation confers resistance to oxidative stress and extends the lifespan of adult flies by inducing the expression of protective genes (Wang et al, 2003).…”
Section: Jnk and Tgf-ˇ Pathwaysmentioning
confidence: 99%
“…The phosphorylation was observed only with the N-terminal (amino acids 83-307) fragment of DAF-16. Furthermore, it has been demonstrated that JNK-1 directly interacts with, phosphorylates, enhances nuclear localization of DAF-16, and induces its target gene expression [24]. Indeed, low levels of oxidative stress generated by treatment with H 2 O 2 activates the small GTPase Ral and induce a JNK-dependent phosphorylation of Threonine 447 and Threonine451, nuclear translocation, and transcriptional activation of FOXO4 [26].…”
Section: Regulation Of Foxos By Other Signaling Pathwaysmentioning
confidence: 99%